PERFORMANCE EVALUATION OF EXISTING SPECIAL BRIDGES IN INDONESIA BASED ON SNI 1725:2016 AND SNI 2833:2016 (CASE STUDY OF DR. IR. SOEKARNO BRIDGE) - Sinatra, Frans; Riyansyah, Muhammad; Suarjana, Made (Jurnal Teknik Sipil, 2020)
AbtractExisting special bridges such as cable-stayed bridges which are complex in structure need to be evaluated against SNI 1725:2016 and SNI 2833:2016. Dr. Ir. Soekarno Bridge located in Manado, North Sulawesi, was used as case study. Analysis based on the performance of the bridge was conducted using the Nonlinear Static Pushover Analysis (NSPA) with three different load distributions and Nonlinear Time History Analysis (NLTHA). Due to the standard load of the bridge, the deflection was still below the allowable deflection. Girder has an overstress of 12% in the Service Ic combination. The cable also has overstress in Cable 7 between 0.4% and 6.2%. Lower segment pylon capacity was exceeded by earthquake load combination of 28%. Bridge performance shows that the bridge structure was at fully operational performance level and the element performance was at immediate occupancy level, each method shows different result in base shear and displacement. The result shows that re-evaluation for existing special bridges is required. The bridge performance has different base shear and displacement for each method. Nonlinear Time History Analysis is the better option for special bridge, Nonlinear Static Pushover Analysis method requires a further study to determine the ideal load distribution for special bridge because the load distribution is crucial to determine the result of pushover analysis. AbstrakJembatan khusus eksisting seperti jembatan cable stayed yang sangat kompleks perlu dievaluasi kinerjanya terhadap SNI 1725:2016 dan SNI 2833:2016. Studi kasus pada penelitian ini adalah Jembatan DR. Ir. Soekarno di Kota Manado, Sulawesi Utara. Dilakukan pula analisis berdasarkan kinerja dengan Nonlinear Static Pushover Analysis dengan tiga pola beban dan Nonlinear Time History Analysis. Akibat beban standar jembatan, lendutan yang terjadi masih dibawah lendutan ijin. Girder mengalami kelebihan tegangan sebesar 12% pada kombinasi beban Layan Ic. Kabel juga terjadi kelebihan tegangan pada Kabel 7 antara 0,4% sampai 6,2%. Kapasitas pylon segmen bawah terlampaui oleh kombinasi beban gempa sebesar 28%. Analisis kinerja struktur jembatan dengan dua metode didapatkan bahwa tingkat kinerja struktur adalah fully operational dan kinerja elemen adalah immediate occupancy, akan tetapi nilai base shear dan perpindahan berbeda untuk masing-masing metode. Hasil analisis menunjukkan bahwa jembatan khusus eksisting perlu di evaluasi ulang terhadap peraturan terbaru. Kinerja jembatan dengan dua analisis nonlinier yang dilakukan menunjukkan hasil yang berbeda, Nonlinear Time History Analysis tetap menjadi metode yang lebih baik untuk jembatan khusus sedangkan metode Nonlinier Static Pushover Analysis perlu penelitian lanjutan untuk menentukan distribusi beban pushover yang cocok digunakan untuk jembatan cable stayed, mengingat pola distribusi beban sangat menentukan hasil dari analisis pushover.